Uncle Wiggily's June Bug friends - Garis, Howard Roger, 1873-1962; Campbell, Lang, 1882-1937 (Salt Lake City, UT : Project Gutenberg, 2023)
"Uncle Wiggily's June Bug friends: or, How the June Bugs brought joy to Uncle Wiggily" by Howard R. Garis is a charming children's storybook that was likely written in the early 20th century. This delightful tale follows the adventures of Uncle Wiggily, a kind bunny rabbit gentleman, and centers around themes of friendship, kindness, and the joy of helping others. The narrative is wonderfully illustrated and appeals primarily to young audiences, as it combines humor with imaginative storytelling. In this book, Uncle Wiggily demonstrates his gentle character by rescuing a June Bug and offering it a place to sleep in his garden. When Uncle Wiggily and two goat children fall into a pit dug by the mischievous Bazumpus, it is the very June Bug he previously helped that comes to their rescue. With the assistance of numerous other June Bugs, they construct a grass ladder that allows the trio to escape. The story continues with Uncle Wiggily encountering another adventure involving a skillery-scallery alligator and a humorous mishap with paint, showcasing the whimsical nature of the characters and their interactions. Ultimately, the book concludes with a lighthearted resolution that reinforces the importance of friendship and community support. (This is an automatically generated summary.)
Release date is 2023-04-23
Bob Taylor, David Edwards and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Flowers -- Juvenile fiction; Rabbits -- Juvenile fiction; Alligators -- Juvenile fiction; Uncle Wiggily (Fictitious character) -- Juvenile fiction; Beetles -- Juvenile fiction